ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA PT. LYNEA PRIMISIMA - Nani Widya (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
PT. Lynea Primisima is a company engaged in the sale of baby products. The company is still using manual system in running its business and it is causing problems in the data processing, delays of information delivery, and the result of the reports not accurate. The purpose of this paper is to do analysis and design information system that can provide suggestions for company to overcome existing problems. The computerized system is also designed, to facilitate all transactions in each division thus improving the quality of the company’s performance. The design method that is used for the system is System Development Life Cycle (SDLC) method. The divisions include sales & marketing, import, finance,warehouse, and personnel. The design of system has a function that processes data storage of employees, stuff, suppliers, and customers; manage the process of selling and buying; manage cash; managing inventory in the warehouse; calculate salary; and preparing reports. Key words analysis and design, information system, company